Monitoring Motor Skills of Children and Adolescents in LIFE Child - Lang, J.; Warnatsch, C.; Vogel, M.; Kirsten, Toralf; Kiess, W. (2014-Leipziger-Research-Festival, 2014)
Life Child is an epidemiological study running at the LIFE Research Center for Civilization Diseas-es (University of Leipzig) since 2011. It aims at monitoring the development in children and adolescents by examining thousands of children in and around Leipzig. Of particular interest in this study are motor skills and physical activities of children between 6 and 18 years. There are multiple examinations including interviews, self-completed questionnaires and physical examinations (e.g., sport tests) to generate data describing the determined child as well her lifestyle and environment. The goal is to find causes for low to non physical activity and unincisive motor skills and capabilities since they are commonly attended with diseases, such as obesity and diabetes. As a first step in this direction, we analyzed data of specific sport tests, such as pushups, side steps and long jumps, according to the body mass index (BMI) of participants. We found that participants with high BMI achieve a similar number of pushups in early years like the normal BMI group, while in later years the pushup number of participants with normal BMI exceeds the pushup number of high BMI group. Surprisingly, the number of side steps is indifferent over age categories (6-18, yearly) between both groups. Conversely, the normal BMI group achieve higher distances through-out all age categories than the high BMI group. In future, we will associate these results with socio-economic and lifestyle indicators, e.g., interest in sport and physical activities of child and parents.